Analisis Kompetensi Pegawai Pada Kantor Camat Kecamatan Sebangki Kabupaten Landak - Muhammad Zalviwan; SUMIATI (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
This study aims to see how the performance of employees in the subdistrict head office of Sebangki District, Landak Regency by looking at the quality of service to the community. The method used in this research is descriptive qualitative method. The number of respondents used in this study were 31 respondents. To facilitate the measurement of qualitative data, a Likert scale is used. In this study, the variables that became the benchmarks for the writer to analyze the problems in this study were the variables of knowledge, expertise, quality, and cooperation. If seen from the results of the study, the competency analysis of employees at the head office of the sub-district of Sebangki, Hedgehog district, based on the respondents' responses, falls into the good category value.